Influence of country of origin image on brand equity of consumers in Bosnia and Herzegovina: the case of smartphone market - Gluhović, Nikola (Anali Ekonomskog fakulteta u Subotici, 2020)
Consumers pay attention to the country of origin when purchasing imported products and believe that it has a significant impact on the formation of consumer attitude towards branded products. Competition among global smartphone brands is an intense, efficient and effective branding strategy, an important prerequisite for accelerating market growth and gaining a competitive market position. The purpose of this paper is recognized in assessing the impact of country of origin image, perceived quality, brand associations and brand loyalty on the consumer-based brand equity (CBBE) formation process, as exemplified by two global smartphone brands, Samsung and Huawei in Bosnia and Herzegovina. For the purposes of the study, a survey was conducted using a questionnaire on a sample of 315 respondents. The survey results indicate that the country of origin image and perceived quality play a more important role in buyers in Bosnia and Herzegovina for Chinese (Huawei) than South Korean (Samsung) smartphones. This suggests that buyers from Bosnia and Herzegovina are paying more attention to the quality of Chinese compared to South Korean smartphones.